PENINGKATAN KETERAMPILAN MENULIS PUISI DENGAN MODEL AMATI, TIRU, MODIFIKASI MENGGUNAKAN MEDIA GAMBAR PADA SISWA KELAS IV SDN PURWANTORO 2 MALANG - Arif Wicaksono; Dyah Worowirastri Ekowati; Yuliati Yuliati (Taman Cendekia: Jurnal Pendidikan Ke-SD-an, 2019)
This study aimed to: (1) describe the implementation of poem writing skills learning, (2) describe the improvement of poem writing skills through observation, imitation, modification model by using images media on fourth-grade students at SD N Purwantoro 2 Malang City. This research used qualitative research with descriptive research types. This type of research was classroom action research (CAR). Classroom action research consisted of three elements, namely research, action, class. The data in this study was a document on the improving skills for writing poetry from grade IV. The data collection technique utilized interviews, observation, and documentation. This study employed two cycles. The results showed that: (1) poetry writing skills of class IV students by the time before using the observation, imitation, and modification models did not meet the excellent standard yet. (2) poetry writing skills by the time after the two cycles implemented with observation, imitation, and modification using image media showed an increasing result; this can be seen from the increase of poetry writing skills score that was achieved by fourth-grade students of SDN Purwantoro 2 Malang City.